Dementia Care Coordination: Evaluating a Program to Support Caregivers through Collaboration with the Alzheimer's Association and Health Care Partners. (20th December 2022) - McGurin, Nicole E; McCarthy, Liz; Arsenault, Lisa; Showalter, Elizabeth; Patterson, Brooke
Abstract: Background: A dementia diagnosis presents a myriad of non‐medical needs that are burdensome to caregivers and critical for disease management. Most medical professionals lack the time and training to meet these needs for support, education, and resources. The Alzheimer's Association MA/NH Chapter has developed the Dementia Care Coordination program that partners health care providers and payors with dementia care consultants to improve outcomes for caregivers. Dementia Care Coordination is a telehealth‐based program that has provided invaluable support and tools for caregivers to manage the increased challenges and isolation of the COVID‐19 pandemic. This caregiver support and efficacy are vital to the health and well‐being of a person living with dementia. Methods: A mixed‐methods approach was used to evaluate Dementia Care Coordination. Program data were analyzed. A survey measuring self‐efficacy, unmet needs, and satisfaction was distributed to caregivers at baseline and three months and six months post‐referral. Key informant interviews with caregivers supplemented survey results. A survey measuring provider confidence in dementia management and program impact and satisfaction was distributed to referring partners. Case studies with several referring partners provided additional descriptions. Results: Total Referrals for Dementia Care Coordination have increased 91% since the pandemic. Surveys for both caregivers and referring partners found high satisfaction with the program. Key informant interviews with caregivers and case studies with referring partners described the positive impact of the program. Ongoing analyses of the quantitative data from the surveys indicate improvement in unmet needs and self‐efficacy among caregivers and improved provider confidence to manage dementia. Conclusions: Dementia Care Coordination is a successful program to meet the needs of and improve outcomes for caregivers. The support, education, and resources were pivotal in managing the additional stresses of the COVID‐19 pandemic for dementia caregivers. The Alzheimer's Association New England Chapters will use the evaluation data to further improve the program, expand healthcare partners, serve more families, and develop a tool kit for replication in other chapters.